Detection and dissemination of the colistin resistance gene, mcr‐1, from isolates and faecal samples in China. Issue 2 (February 2017) - Chen, Xia; Zhao, Xiaofei; Che, Jie; Xiong, Yanwen; Xu, Yanmei; Zhang, Lifeng; Lan, Ruiting; Xia, Lining; Walsh, Timothy R; Xu, Jianguo; Lu, Jinxing; Li, Juan
Abstract : Purpose. : A recently identified colistin resistance gene, mcr‐1, has been reported in many countries. In this study, we established a new real‐time PCR method to detect it. Methodology. : We used a real‐time PCR method to detect the mcr‐1 gene in a variety of isolates and faecal samples from 20 provinces and municipal cities in China. Results. : Of the 2330 isolates (from 10 species) screened, 54 (2.3 %) isolates were positive for mcr‐1 . All of the mcr‐1 ‐positive isolates that were identified belonged to Escherichia coli strains, among which 9, 1, and 44 were identified as enteropathogenic E. coli, enteroadherent E. coli, and non‐pathogenic E. coli, respectively. The majority of the mcr‐1 ‐positive isolates were obtained from farm animals from eight provinces and municipal cities across China. A total of 337 faecal samples, including 229 human and 108 pet animal faecal samples, were also screened for the mcr‐1 gene. Of the 337 samples analyzed, six and eight human and pet animal faecal samples were positive for the mcr‐1 gene, respectively. Conclusion. : The data demonstrate that the mcr‐1 gene is highly prevalent in human and animal populations in China. This occurrence suggests that active surveillance of the mcr‐1 gene is imperative in curtailing its spread.